ANALYSIS OF THE FACTORS LEADING PRIVATE FOREST CONVERSION IN UPSTREAM CILIWUNG WATERSHED - Agus Astho Pramono; Aam Aminah (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2010)
Land degradation resulted from mismanagement of upstream watershed is one of the serious threats to the downstream areas. Deforestation and land degradation caused by forest conversion in upstream Ciliwung watershed havecaused annual floods to its downstream region. This research aims to answer problems regarding: 1) factors leading to develop agroforestry, 2) the best land use chosen by the community in upstream Ciliwung watershed. Samples respondents were taken by purposive manner. The analysis were carried out by using regression logit and land rent calculated based net present value analysis. The result of this research revealed that the existence of agroforestry system are influenced by occupation and land elevation. Agroforestry is not interesting land use choice of upstream Ciliwung watershed farmers. Vegetable crop is the best choice of the most farmers.